Scott Pilgrim takes off [videorecording (Blu-Ray)] : the complete limited series - O'Malley, Bryan Lee; Grabinski, BenDavid, 1983-; O'Malley, Bryan Lee (Universal, 2025)
Based on the cult classic live-action film Scott Pilgrim vs. The Word, Scott Pilgrim returns in an 8-part animated series. The original film cast reprise their roles in Scott Pilgrim Takes Off : The Complete Limited Series. Scott meets the girl of his dreams, Ramona Flowers, but learns he must defeat her seven evil exes to date her. Then things get even more complicated. Based on the graphic novels by Bryan Lee O'Malley, this is Scott Pilgrim like you've never seen before!